Sensitive nonradioactive dot blot/ribonuclease protection assay for quantitative determination of mRNA - Zhan, Jinghai; Fahimi, H. Dariush; Völkl, Alfred (BioTechniques, 1997)
We have developed a simple and sensitive method for the rapid quantitation of mRNA from cell cultures and small tissue samples. The method combines the high sensitivity and specificity of the ribonuclease protection assay with simple handling and rapid execution of dot blotting. The use of digoxygenin-labeled cRNA probes eliminates all problems associated with radioisotopes commonly used in the ribonuclease protection assay. The RNA preparation is dotted directly onto nylon membranes, and after hybridization the filters are treated with ribonuclease A, which removes the nonhybridized single-stranded RNA. The mRNA-hybrid is then visualized by the chemiluminescence technique using labeled anti-digoxigenin antibody, and the signal intensity is quantitated. Comparison with the Northern blotting ribonuclease protection assay revealed that this dot blot technique is almost ten times more sensitive and that its signals are linear over a wide range of RNA concentrations (0.01-10 μg/μL/ dot). This method seems particularly valuable for simultaneous processing of large numbers of samples containing a wide range of RNA concentrations.